MODEL AMBANG BATAS FISIK DALAM PERENCANAAN KAPASITAS AREA WISATA BERWAWASAN KONSERVASI DI KOMPLEKS CANDI GEDONG SONGO KABUPATEN SEMARANG - Hayati, Rahma (Jurnal Geografi, 2013)
This study have the following objectives: 1. Knowing the threshold value oftourist numbers in temple cultural tourism area according to physical carryingcapacity, 2. Knowing the threshold value of tourist numbers in temple culturaltourism area according to ecological carrying capacity, 3. Knowing the thresholdvalue of tourist numbers limitation in camp area according to physical carryingcapacity, as well as, 4. Knowing the threshold value of tourist numbers in camparea according to ecological carrying capacity. The threshold values calculatedby the Douglas method (1975) in Fandeli (2001). The results of the thresholdvalues calculation are as follows: 1. The threshold value of tourist numbers incultural tourism area according to physical carrying capacity is 514 people /acres, 2. threshold value of tourist numbers in cultural tourism area according toecological carrying capacity is 9,374 people / acres, 3. threshold value of touristnumbers in camp area according to physical carrying capacity is 3 persons /acres, and 4. threshold value tourist numbers in camp area according toecological carrying capacity is 40 people / acres.